Perancangan Strategi Peningkatan Kualitas Layanan Agen X Milik PT Abc Menggunakan Metode Servqual Di Wilayah Jabodetabek - Simbolon, Tigor Rizkiadi; Nadlifatin, Reny (Jurnal Pendidikan Indonesia, 2025)
Bank agency services are services that aim to expand access to financial services for the public. In support of this, PT ABC presents agency services under the name of Agent X such as money deposit transactions, cash withdrawals, transfers, purchases, bill payments and other bank services. Although the number of Agent X continues to increase and reaches 747,818 agents in 2023, the growth in the number of transactions, sales volume, and service revenue has actually decreased. In fact, there are still findings in the field showing that there are customer complaints about the quality of services provided by Agent X such as services that are not uniform, old and not as expected. This study aims to design a strategy to improve the quality of Agent X services in the Greater Jakarta area using the ServQual method. The ServQual method was used to measure the level of gap between perception and expectations as well as the level of customer interest obtained through filling out a questionnaire by Agent X customers with a total of 400 respondents. Based on the results of ServQual’s analysis, it was found that the highest gap between customer perception and expectations in the dimensions of responsiveness, assurance and reliability.